Differences in psoriasis signs and symptom severity between patients with clear and almost clear skin in clinical practice. (3rd May 2016) - Feldman, Steven R.; Bushnell, Donald M.; Klekotka, Paul A.; Scanlon, Michael; Martin, Mona L.; Wade, Sally W.; Yang, Wenjing; Pinto, Lionel; Kircik, Leon; Viswanathan, Hema N.
Abstract: Introduction : In psoriasis clinical trials, treatment success is often defined as achieving a static Physician Global Assessment (sPGA) score of 0 (clear) or 1 (almost clear). Patients with clear versus almost clear skin may experience psoriasis differently. This study assessed whether aggregating these patients underestimates subjective improvements associated with total skin clearance. Methods : Patients with plaque psoriasis with stable sPGA 0 or 1 currently treated with adalimumab, etanercept, infliximab, or ustekinumab reported Psoriasis Symptom Inventory (PSI) scores for seven days and Dermatology Life Quality Index (DLQI) scores on day 8. The PSI measures psoriasis signs and symptom severity; the DLQI measures the impact of skin disease on quality of life. This analysis compared PSI and DLQI outcomes between patients with sPGA 0 and 1. Results : This study assessed 230 patients: 79 sPGA 0 and 151 sPGA 1. A greater percentage with sPGA 0 than sPGA 1 achieved a total PSI score of 0 ("best"; 61% vs. 5%, p < 0.0001) and DLQI 0 ("no effect"; 79% vs. 24%, p < 0.001). Patients with sPGA 0 reported better scores than sPGA 1 on all other PSI and DLQI assessments. Conclusions: Achieving total skin clearance, compared with almost clear skin, provides clinically meaningful improvements in psoriasis.